Youth Entrepreneurship in Russia: Searching for Alternatives of Development - I. E. Belskikh (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
The article studies possible alternatives of youth entrepreneurship development in Russia in view of expert opinion. By analyzing empiric and normative material and using national experience three approaches to solving the problem were identified: 1) from the standpoint of socialization and all-round development of young people; 2) from the point of view of Russian-Belorussian experience (enthusiasm for standard guidelines, formal methods of reporting and regional budget co-financing of projects); 3) within the frames of realization of virtual, digital entrepreneurial activity based on universities. In view of author’s opinion concerning youth entrepreneurship development in Russia priorities were fixed. The author showed the demand for setting-up enterprises for concrete industries in the international format (support of project competitions based on effective youth companies with the help of tax policy); changing normative and administrative paradigm in regulator’s behavior on market for the youth (establishing norms and practices as summarizing effects of mass success of real projects but not advance fixing of standards and responsibilities); growing importance of the private sector in the development of youth business (intensifying motivation and interest in social nets and mass media); using mechanisms of venture financing and the role of business-angels on the basis of regional and federal business-leaders; refusal to use universities in the development of youth business. The author also proposed tools of alternative development of entrepreneurship in youth quarters based on private initiatives. Alternative development implies universal changes in promoting projects in Russian society and on markets.